"Felony assault should stick:" Assaulted EMS responders' frustration and dissatisfaction with the legal system. Issue 11 (16th August 2019) - Wright, Jasmine Y.; Davis, Andrea L.; Brandt‐Rauf, Sherry; Taylor, Jennifer A.
Abstract: Introduction: The prevalence of violence to first responders is reported in ranges of approximately 40% to 90%. Pennsylvania has a felonious assault statute to address such violence, but the prosecutorial process has been noted to cause first‐responder dissatisfaction. Methods: An exploratory qualitative study using individual interviews with snowball sampling was conducted with the Philadelphia District Attorney's office to understand the prosecutorial process when a first responder is assaulted and injured in a line of duty. The Philadelphia Fire Department provided a list of first responders who sustained a work‐related injury from a patient or bystander assault so that particular cases could be discussed during the interviews. Results: Emergent themes fell into two categories: factors that lead to a charge (prosecutorial merit, intent, and victim investment), and the judge's discretion in sentencing ("part of the job" mentality, concern for the defendant, and the justice system's offender focus). Immediately actionable tertiary prevention recommendations for fire departments, labor unions, and district attorney's offices were developed. Conclusion: Violence against fire‐based emergency medical service (EMS) responders is a persistent and preventable workplace hazard. While felonious assault statutes express society's value that it is unacceptable to harm a first responder, this study found that such statutes failed to provide satisfaction to victims and that support when going through the court process is lacking. Assaulted EMS responders, their employers, and labor unions would benefit from the recommendations provided herein to help them extract a stronger sense of procedural justice from the legal process.